Dry eye syndrome - vicious circle mechanism of disease - Dybała, Ewelina; Dybała-Przygrodzka, Izabela; Aghadi, Artur; Cuber, Iwona; Białowąs, Edyta; Mazurek, Magdalena (Journal of Education, Health and Sport, 2023)
The correct structure of the tear film ensures the appropriate degree of hydration of the eye surface, and has a protective and nourishing function. Irregularities in the structure of one of the three layers of the tear film can contribute to dry eye syndrome. In recent studies, scientists have focused on dysfunction of the Meibomian gland and on deficiencies in the lipid layer of the tear film, which led to the evolution of preparation complementing the tear film. Dry eye syndrome is a multifactorial disease of the ocular surface. Symptoms vary from itching, burning, irritation, eye strain and eye inflammation to potential complications that include damage to the cornea, conjunctiva, and even loss of vision. Blurred vision is a component of the definition of DSO (apart from discomfort, tear film instability, changes in tear osmolarity, changes in neurosensory and specific inflammation on the surface of the eye). Changes in the thickness of the tear film translate into changes in the breaking power of the eye. It is believed that for every 0.1 mm change in tear film thickness, there is 0.5 D in the "+" or "-" direction. The result of aberration is the lack of a sharp, dotted image.Treatment is adjusted individually for each patient, based on the underlying disease mechanism. Recent studies have shown that dry eye is an inflammatory disease that shares many characteristics with autoimmune diseases. The main goal of this work is to present an outline of epidemiology, pathogenesis, risk factors and treatment methods.